(3eONd JMbjb GdQVG GdhXjajs - (3Hf eMeO GdCNVQ(B, (3eMLhHjs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2021)
(3GdGWGQ GdYGe ddJShjb GdOGNdj hGdeUOGbjI, eagheg heQGMd JWhQg, NUGFUg hYdGbJg HHYV GdeaGgje GdGOGQjI ef GOGQI GdLhOI GdTGedI hGdKbGaI GdJfXjejI, eY PcQ HYV CfTWI hGLQGAGJ JfajP GdJShjb GdOGNdj cfehPL HjQj hfehPL cQhfQhS hcPdc fehPL Qajb hCMeO ddJShb GdOGNdj, HGdGVGaI Gdi eUOGbjI efXeI GdNOeGJ ef GOGQI GdefGN GdOGNdj eY LhOI GdNOeI GdOGNdjI hcPdc GOGQI JhbYGJ GdRHGFf, heGgjI GdQVG GdhXjaj hGjVG HYV feGPL hfXQjGJ gPG GdCNjQefgG fXQjI GdMGLI hGdYGedjf dgjQRHQL hGdebGQfI(B.(3hCNjQG GdJShb GdOGNdj aj Xd HYV GdJLGQH GdYQHjI hGdCLfHjI(B.s
(3eQGLY U(B.157s
Keywords: (3GOGQI GdJShjbs; (3GdQVG GdhXjajs